2013
DOI: 10.4028/www.scientific.net/amm.318.331
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Failure Analysis of N80 Q Marine Casing

Abstract: The 13-3/8〞casing of a well was bent down and broken off in the marine development completion process. The cause for the fracture is systematically analyzed by means of chemical composition analysis, mechanical properties testing, macro and micro fracture analysis and metallographic analysis. The results indicate that, the heterogeneity of the casing material and large oxide metallurgical inclusions found in fracture place severely reduce the properties of the material, which lead to the failure of casing pipe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Regarding the fracture failure of the threaded connection, zhang xu found that the casing material presented brittleness at low temperature, and local stress concentration occurred on the surface of the casing tube, which resulted in brittle fracture of the casing tube [1]. Zeng zhong proposed that non-standard operation in the upper shackle would lead to the increase of local contact stress in the thread segment and the increase of thread advance resistance, aiming at the fracture failure of steel casing of P110 steel grade [2].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the fracture failure of the threaded connection, zhang xu found that the casing material presented brittleness at low temperature, and local stress concentration occurred on the surface of the casing tube, which resulted in brittle fracture of the casing tube [1]. Zeng zhong proposed that non-standard operation in the upper shackle would lead to the increase of local contact stress in the thread segment and the increase of thread advance resistance, aiming at the fracture failure of steel casing of P110 steel grade [2].…”
Section: Introductionmentioning
confidence: 99%